Three features of aging in the People Republic of China and implications for development agenda. - Terada-Hagiwara, Akiko; Park, Donghyun; Van Rijn, Hans (ADB Briefs, 2018)
This ADB brief explores policy options that can help the People Republic of China prepare for an aging population. The People Republic of China (PRC) demographic transition is unique in terms of its (i) speed, (ii) increase in the elderly dependency ratio, and (iii) the slow progress in preparing for it. Aging is progressing fast, even as the country is still developing the necessary soft and hard infrastructure to respond. In particular, addressing the challenge of developing a long-term elderly care system requires a rethink of delivery models, as well as reforms in pension and insurance systems. Infrastructure development also needs to cater to the needs of elderly citizens. This note provides possible directions to respond to the socioeconomic and fiscal impacts of aging.